Variants of Callous–Unemotional Traits in Middle Childhood: An Investigation of Emotional Regulation, Externalizing Behaviors, and Psychosocial Risk Factors - Yu Gao; Ines Guariguata; Liat Kofler (Children)
Background: A growing body of literature suggests that there are two variants of callous–unemotional (CU) traits—primary (with low anxiety) and secondary (with high anxiety)—although whether these traits differ in emotional regulation is unknown. The present study aimed to further our understanding of these variants by comparing the two variant groups (high CU/low anxiety and high CU/high anxiety) with two control groups (low CU/low anxiety and low CU/high anxiety) on emotional regulation, along with a variety of psychosocial and externalizing behavioral measures. Methods: A community sample of children aged 8 to 10 years (N = 340) from the northeast United States and their main caregivers participated in this study. Children completed an emotional regulation task while their sympathetic and parasympathetic nervous system activities were recorded. Prenatal and postnatal adversity and externalizing behaviors of the children were assessed using caregiver and child reports. Results: It was found that children with high CU/high anxiety were characterized by elevated parasympathetic activities during the emotional regulation task, along with more adversity and externalizing behaviors. Conclusions: These findings extend our knowledge on CU by highlighting the emotional dysregulation and more severe clinical picture that were associated with more psychosocial adversity in the high CU/high anxiety variants.